Response Time Analysis for Fixed-Priority Tasks with Multiple Probabilistic Parameters - Maxim, Dorin (2015)
Demo presented in 12th Workshop on Models and Algorithms for Planning and Scheduling Problems (MAPSP 2015). 8 to 12, Jun, 2015. La Roche-en-Ardenne, Belgium. Extended abstract.